Harnessing the Power of Brand Attributes: The Impact on Corporate Brand Image and Customer Loyalty in Indonesian Islamic Banking (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2024)
Despite Indonesia's significant potential for Islamic banking growth due to its large Muslim population, the sector encounters intense competition from conventional banks offering similar products. This necessitates a strong focus on differentiation, with a robust and distinct brand image crucial for the long-term sustainability of Islamic banking institutions. This study investigates factors influencing customer loyalty towards Indonesian Islamic banking. It was built upon prior research on functional, emotional, and spiritual brand attributes by introducing online brand attributes as a novel perspective. The digitalization and innovation phenomenon can act as critical drivers, enhancing competitiveness and broadening service reach through online channels for Islamic banks. Using a quantitative approach with 480 sharia banking customers in Indonesia, the research employed Partial Least Squares-Structural Equation Modeling (PLS-SEM) to examine the role of brand image in fostering customer loyalty. Findings reveal that online brand attributes exerted the most significant positive impact on corporate brand image (CBI). In turn, CBI has positive impacts on customer loyalty. Among the variables examined, core service, beliefs, sharia compliance, and security were found to have the most decisive influence on CBI in Indonesian Islamic Banking.